2011
DOI: 10.1002/jrs.2987
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen vacancy‐induced microstructural changes of annealed CeO2−xnanocrystals

Abstract: Nanocrystalline ceria (CeO 2 ) is known for its ionic conductivity and oxygen storage properties, which depend on the presence of oxygen ion vacancies. The vacancies cause several important changes in CeO 2 involving microstrain, electronic structure, magnetic properties, etc. In this article, we focus our attention to the microstructural changes of nanocrystalline CeO 2−x annealed at different temperatures in the range 200-500 • C. Structural and vibrational properties were investigated by X-ray diffraction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 30 publications
3
44
0
Order By: Relevance
“…(8) has been compared with the stoichiometry determined directly from the intensities of the O 1s and Ce 3d XPS peaks. The A O and A Ce are corresponding to the peak area of O 1s and Ce 3d respectively.…”
Section: Composition and Chemical Statementioning
confidence: 99%
See 1 more Smart Citation
“…(8) has been compared with the stoichiometry determined directly from the intensities of the O 1s and Ce 3d XPS peaks. The A O and A Ce are corresponding to the peak area of O 1s and Ce 3d respectively.…”
Section: Composition and Chemical Statementioning
confidence: 99%
“…CeO 2 is a chemically stable oxide, with an outstanding capacity to store or release oxygen due to the variation of the oxidation state of cerium between +3 and +4 [8]. Because the variation of the oxidation state can lead to oxygen vacancies and Ce 3+ ions, hence, this property can contribute to novel properties.…”
Section: Introductionmentioning
confidence: 99%
“…These oxygen vacancies play an important role to produce magnetism in the oxide nanomaterials. 20,21 Coey et al have suggested that the oxygen vacancies can make a significant contribution to enhance the ferromagnetism by changing the band structure of host oxides. 22 Sundaresan et al 17 have explained the ferromagnetism in CeO 2 NPs in terms of exchange interactions between unpaired spins resulting from oxygen vacancies.…”
Section: +mentioning
confidence: 99%
“…The possibility of the reversible transition from CeO 2 to Ce 2 O 3 makes cerium oxide one of the promising materials, the desired catalytic properties of which can be adjusted by a suitable choice of metal or metal oxide additives. In fact, the substitution of a part Ce 4+ by other suitable cations improves the low temperature reducibility and the oxygen storage capacity of cerium oxide [19]. However, CeO 2 may also be useful for radiation dosimeters [20,21] because nuclear radiations modify the electrical properties of CeO 2 film structures.…”
Section: Introductionmentioning
confidence: 98%